CLINICAL CHARACTERISTICS AND LABORATORY PARAMETERS IN DENGUE HEMORRHAGIC FEVER - Talha Tariq; Aizaz Ali Khan; Noor Ul Amin; Emaan Saeed; Alisha Saleem; Amna Khalid; Syeda Wajiha Rehan; Hafiza Sidra (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Introduction: Dengue is an infection caused by Dengue virus which transmitted by the bite of an infected mosquito.Objectives: The main objective of the study is to find the clinical characteristics and laboratory parameters in Dengue hemorrhagic fever among local population of Pakistan. Material and methods: This cross sectional study was conducted in RYK Teaching Hospital Rahim Yar Khan Pakistan. The data was collected from 200 patients of both genders. Clinical data was collected from medical records and compared between the dengue and control groups included demographic data, clinical presentations and all parameters from the CBC. Results: The results indicate a significant reduction in T-SOD activity in the serum of infected patients (220.15 ± 34.50 U/ml.mg) compared to controls (310.45 ± 39.20 U/ml.mg) (p